Sasaran Dakwah Pada Masa Nabi S.A.W: Kajian Terhadap Sistem Kepercayaan - Mohd Zin, Ab. Aziz (Jurnal Usuluddin, 1995)
The article discusses worshipping activities among the Arab community before Islam, such as belief in God, idolairy and belief in ghosts. Some of the Arabs also worshipped stars, sun and moon.